The Roadmap of Graphene-Based Sensors: Electrochemical Methods for Bioanalytical Applications - Ghazala Ashraf; Ayesha Aziz; Tayyaba Iftikhar; Zi-Tao Zhong; Muhammad Asif; Wei Chen (Biosensors, 2022)
Graphene (GR) has engrossed immense research attention as an emerging carbon material owing to its enthralling electrochemical (EC) and physical properties. Herein, we debate the role of GR-based nanomaterials (NMs) in refining EC sensing performance toward bioanalytes detection. Following the introduction, we briefly discuss the GR fabrication, properties, application as electrode materials, the principle of EC sensing system, and the importance of bioanalytes detection in early disease diagnosis. Along with the brief description of GR-derivatives, simulation, and doping, classification of GR-based EC sensors such as cancer biomarkers, neurotransmitters, DNA sensors, immunosensors, and various other bioanalytes detection is provided. The working mechanism of topical GR-based EC sensors, advantages, and real-time analysis of these along with details of analytical merit of figures for EC sensors are discussed. Last, we have concluded the review by providing some suggestions to overcome the existing downsides of GR-based sensors and future outlook. The advancement of electrochemistry, nanotechnology, and point-of-care (POC) devices could offer the next generation of precise, sensitive, and reliable EC sensors.